Bacterial nanocellulose as novel carrier for intestinal epithelial cells in drug delivery studies - Fey, Christina; Betz, Jana; Rosenbaum, Corinna; Kralisch, Dana; Vielreicher, Martin; Friedrich, Oliver; Metzger, Marco; Zdzieblo, Daniela (Materials Science and Engineering C, 2020)
Synthetic cell carriers (A) represent common scaffold structures for the development of cell-based in vitro models of the human intestine but due to their low porosity or unwanted molecular adhesion effects, synthetic carriers can negatively affect cell function. Alternative scaffolds such as natural extracellular matrices (ECMs) (B) were shown to overcome some of the common drawbacks. However, their fabrication is time-consuming, less well standardized and not entirely conform to the 3R principle (replacement, reduction, refinement). Nowadays, biopolymers such as bacterial nanocellulose (BNC) (C) represent interesting scaffold materials for innovative tissue engineering concepts, as they can be generated in a faster and more standardized process workflow without the need for animal material. In this study, we demonstrate the BNC as suitable carrier for the development of Caco-2-based in vitro models of the human intestine. The BNC-based models exhibit organ-specific properties comprising typical cellular morphologies, characteristic protein expression profiles, representative ultrastructural features and the formation of a tight epithelial barrier. The proof of in vivo-like transport activities further validates the high quality of the BNC-based Caco-2 models. In summary, this illustrates the BNC as alternative bioscaffold of non-animal origin to develop functional organ models in vitro.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Bacterial nanocellulose (BNC); Caco-2 cells; Extracellular matrix (ECM); Small intestinal submucosa (SIS); Transwell®-like intestinal models